Elizabeth Wolstenholme Elmy and the Victorian Feminist Movement : the Biography of an Insurgent Woman. - Wright, Maureen (Gender in history., 2011)
This book provides the first full-length biography of Elizabeth Wolstenholme Elmy (1833-1918) - someone referred to among contemporaries as?the grey matter in the brain? of the late-Victorian women?s movement. A pacifist, humanitarian?free-thinker?, Wolstenholme Elmy was a controversial character and the first woman ever to speak from a public platform on the topic of marital rape. Lauded by Emmeline Pankhurst as?first? among the infamous militant suffragettes of the Women?s Social and Political Union, Wolstenholme Elmy was one of Britain?s great feminist pioneers and, in her own words, an.